The medium- and long-term outcome of total shoulder arthroplasty for primary glenohumeral osteoarthritis in middle-aged patients - Sowa, Boris; Bülhoff, Matthias; Zeifang, Felix; Loew, Markus; Bruckner, Thomas; Raiss, Patric (The bone & joint journal, 2017)
Aims: Promising medium-term results from total shoulder arthroplasty (TSA) have been reported for the treatment of primary osteoarthritis in young and middle-aged patients. The aim of this study was to evaluate the long-term functional and radiological outcome of TSA in the middle-aged patient.Patients and MethodsThe data of all patients from the previous medium-term study were available. At a mean follow-up of 13 years (8 to 17), we reviewed 21 patients (12 men, nine women, 21 shoulders) with a mean age of 55 years (37 to 60). The Constant-Murley score (CS) with its subgroups and subjective satisfaction were measured. Radiological signs of implant loosening were analysed. Results: Two shoulders (two patients) were revised and in two shoulders of two different patients, revision surgery was recommended. The mean CS increased from 23.3 (10 to 45) pre-operatively to 56.5 (26 to 81; p < 0.0001), but with a decrease in CS from 62.8 (38 to 93) to 56.5 (26 to 81) between medium- and long-term follow-up (p = 0.01). Without revision surgery, 18 patients (95%) rated their result as good or very good.The mean radiolucent line score for the glenoid components increased from 1.8 (0 to 6) to 8.2 (2 to 18) between medium- and long-term follow-up (p < 0.001). Conclusion: TSA in young and middle-aged patients leads to improvement in clinical function and a relatively high satisfaction rate. However, clinical or radiological glenoid loosening worsens in the long term. Further studies are needed to optimise the treatment options in this patient population.